Percutaneous Nerve Evaluation (PNE) for Treatment of Non-Obstructive Urinary Retention: Urodynamic Changes, Placebo Effects, and Response Rates - Sharifiaghdas, Farzaneh; Mirzaei, Mahboubeh; Ahadi, babak (Urology Journal, 2014)
Purpose: To evaluate the results of percutaneous nerve evaluation (PNE) implantation in the treatment of non-obstructive urinary retention and report the changes in the urodynamic parameters. Materials and Methods: Patients with non-obstructive urinary retention or incomplete bladder emptying were included. All patients filled a 7 days voiding diary chart and underwent PNE for one week, and the patient was asked to record the second voiding diary chart and repeat urodynamic study in this period. Then the PNE lead was removed from the S3 foramen, but the connections remained fixed in place for another 3 days to exclude the placebo effects and the third voiding diary chart was completed by the patient. The patient wasn’t aware of lead removal. Success was defined as, more than 50% improvement in at least one of the urinary tract symptoms. Results: Forty five patients with a mean age of 37.1 years (ranged 9-83 years) were treated with PNE for refractory, non-obstructive urinary retention. Of study subjects 28 complained from complete urinary retention, and 17 had incomplete emptying. Of participants, 28 (62.2%) demonstrated greater than 50% improvement in the urinary symptoms. Urodynamic data, showed a statistically significant increase in maximum flow rate (8 ± 2.2 mL/sec to 16 ± 3.6 mL/sec, P = .06) and voided volume (35 mL to 187 mL, P = .032) in the responders. Any placebo effects in PNE have not been seen. Conclusion: Patients with complete non obstructive urinary retention were good responders to PNE. The placebo effect in sacral nerve stimulation was negligible.